Defining economic typologies based on an economic activities database. - Giaretta, Federico; Pennincx, Inge; De Mulder, Sophie; Zaman, Jan (My University, 2018)
Economy and especially economic activities play a fundamental role in cities and in surrounding areas: it keeps the city functioning, in terms of jobs, goods and services. Considering this fundamental role of economy and economic activities and the vast amount of space it uses, it should be deeply studied and understood in order to guarantee a solid future to the sector itself and the cities. This paper respesents an attempt to research more in depth this matter: it tries to show how economy is organised and structured in a city and surrounding areas and how it can be analysed and considered by policy makers. The aim is to define economic types that represent the frame on which different types of spatial policies, ideally one for each economic location type, should be developed and implemented by policies makers. The project is based on a visual economic activities database. This contains information on all the visible economic units where people work or that are meant to be worked in. The study areas are the northern part of Brussels and two other areas located in Flanders (Belgium). Thanks to this visual inventory, we first tried to define a GIS methodology that defines and subdivides the economic fabric into different areas, according to the concentration of economic activities. This work is based on the hypothesis that the morphology of parcels with economic units on them is an indicator of location choice of companies. Secondly, we combined the database of economic activities with the data on economic fabric concentration in order to define and analyse different economic location types which represent potential economic locations for companies. In this paper we will explain the method used for the data elaboration and the difficulties encountered during the work. We will also discuss how this new economic location types could be used as an instrument in a planning or policy process to define the future perspective for a specific area.
Keywords: Unternehmensansiedlung; Wirtschaftsstandort; Regionalwirtschaft; Wirtschaftsstruktur; Standortfaktor; Standortwahl